Analysis of the corrosive effects of hydrochloric acid (HCl) on human bone: Preliminary microscopic study and observations for forensic purposes. (December 2021) - Guendalina, Gentile; Stefano, Tambuzzi; Salvatore, Andreola; Paolo, Bailo; Giorgia, Bilato; Ilaria, Gorini; Riccardo, Zoja
Highlights: Cadavers in acid are difficult forensic situations. Destruction of human bone in hydrochloric acid (HCl). HCl 37% is more destructive than HCl 10%. Cortical bone is more resistant than spongy bone to acid. Recognizability as human bone tissue may be lost. Abstract: The destruction of a corpse in caustic acid can cause complex forensic scenarios to deal with. Furthermore, the literature on the subject is poor, having been the few studies carried out only on animal bones. We carried out an experimental analysis on human cranial, ribs, vertebrae, and femur bone fragments. These samples were sent for dissolution by hydrochloric acid (HCl) at two different concentrations in the lab: 10% and 37%. We have performed macroscopic and microscopic histological and cytological observations at set time intervals: 3, 4, 19, 24, 48, and 72 h of immersion in acids. The purpose of the study was threefold: to investigate the temporal evolution of bone dissolution, evaluate the destructive effect of the two hydrochloric acids, and establish whether or not the human pattern of histological structure could be recognized. A more significant destructive action of HCl at 37% has been observed. In the 10% acid, the bone nature of the samples was demonstrable up to 24 h of immersion, but the human pattern of histological structure was already compromised at 19 h, being lost at 24 h. Instead, in the 37% acid, the bone nature of the sample was demonstrable only within 4 h of immersion, and the human pattern of histological structure was markedly compromised within 3 h. At 19 h of immersion, neither the recognition of the bone nor its human nature was feasible. These preliminary findings and observations may be of practical use in forensic investigations of bodies found in acidic substances, for which there is no scientific evidence to refer.